Surgical Management of Lung Gangrene - Baiya Krishnadasan; Vandy L Sherbin; Eric Vallières; Riyad Karmy-Jones (Canadian Respiratory Journal)
OBJECTIVE: To review the outcomes of five cases of pulmonary resection for lung gangrene.